2000
DOI: 10.1161/01.res.86.3.319
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxic Regulation of Inducible Nitric Oxide Synthase via Hypoxia Inducible Factor-1 in Cardiac Myocytes

Abstract: The relationship between hypoxia and regulation of nitric oxide synthase (NOS) in myocardial tissue is not well understood. We investigated the role of hypoxia inducible factor-1 (HIF-1) on expression of the inducible NOS (iNOS) in myocardial cells in vivo and in vitro. In situ hybridization in myocardial tissue from rats exposed to hypoxia for 3 weeks demonstrated increased iNOS mRNA expression. Northern analysis of RNA from hearts of those animals and from cells exposed to hypoxia for 12 hours in vitro demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
201
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(214 citation statements)
references
References 50 publications
8
201
1
4
Order By: Relevance
“…It is known that hypoxic activation of iNOS transcription is mediated by HIF in cardiomyocytes (19,25). The increase of iNOS mRNA levels by the infection of cultured neonatal cardiomyocytes with Ad2/HIF-1␣/VP16 or Ad2/HIF-1␣/ NF-B implies that the upregulation of this protein is an important protective mechanism by expression of a constitutively stable hybrid HIF-1␣ in this particular experimental setting.…”
Section: Fig 1 Effects Of Preconditioning (Pc) On Cell Viability (Amentioning
confidence: 94%
See 2 more Smart Citations
“…It is known that hypoxic activation of iNOS transcription is mediated by HIF in cardiomyocytes (19,25). The increase of iNOS mRNA levels by the infection of cultured neonatal cardiomyocytes with Ad2/HIF-1␣/VP16 or Ad2/HIF-1␣/ NF-B implies that the upregulation of this protein is an important protective mechanism by expression of a constitutively stable hybrid HIF-1␣ in this particular experimental setting.…”
Section: Fig 1 Effects Of Preconditioning (Pc) On Cell Viability (Amentioning
confidence: 94%
“…It has been suggested that AP-1 and NF-B may mediate the transcriptional activation of several mediators that are involved in ischemic preconditioning (22,36). It is also known that transcription of iNOS, an important mediator/effector of myocardial preconditioning (8), is directly activated by HIF-1 in response to hypoxia (9,12,19,32). Protection of rat brain and retinal tissues against subsequent lethal ischemia by prior exposure to sublethal hypoxia is associated with elevated levels of the HIF-1␣ protein (6,7,14).…”
Section: Fig 1 Effects Of Preconditioning (Pc) On Cell Viability (Amentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxiainducible-factor-1 is an important component of a widely operative transcriptional response, activated by hypoxia, cobaltous ions, and iron chelation. Hypoxia-inducible-factor 1 activates transcription of hypoxia-inducible genes, including those encoding erythropoietin (Wang and Semenza 1993), vascular endothelial growth factor (VEGF) (Forsythe et al, 1996), heme oxygenase-1 (Hoetzel et al, 2001), inducible nitric oxide synthase (Jung et al, 2000), and the glycolytic enzymes aldolase A, enolase 1, lactate dehydrogenase A , phosphofructokinase I (Minchenko et al, 2002), and phosphoglycerate kinase I (Li et al, 1996). The C-terminal of HIF-1a binds to p300, and p300/CBP-HIF complexes participate in the induction of hypoxia-responsive genes, including VEGF (Arany et al, 1996).…”
mentioning
confidence: 99%
“…Expression of HIF1α mRNA and protein is induced in the brains of neonatal rats following hypoxia, intraperitoneal injection of cobalt chloride or desferrioxamine, and this up-regulation is associated with protection against cerebral infarction following hypoxia and ischemia [28] . HIF1α expression is also likely to be involved in cardiac preconditioning because NOS2 expression is essential for late preconditioning, and an intact HIF1 DNA binding site in the NOS2 promoter is required for its transcriptional induction in hypoxic myocardial cells [29] . Previous reports demonstrated that HIF1 interacts with the iNOS promoter directly in myocardial extracts after intermittent hypoxic preconditioning by using chromatin immunoprecipitation assay (CHIP) analysis [30] .…”
Section: Discussionmentioning
confidence: 99%